(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The COVID-19 pandemic spread a worldwide crisis that has significantly impacted businesses globally, including firms in Lebanon. This paper investigates and sheds light on the corporate strategic choices adopted by Lebanese companies to steer through this unprecedented crisis. The study explores various strategies adopted by the organizations, ranging from structural modifications to the diversification of products and services and even operations shut-down. Additionally, it analyzes the move towards digitalization and remote work and the implementation of new directions to ensure business continuity. Those are assessed based on qualitative research using in-depth interviews with a conveniently selected sample of 22 Lebanese organizations spanning several economic sectors. Results are commensurate to the challenges faced by companies in Lebanon, such as limited resources, political instability, and economic downturn. The findings suggest that companies in Lebanon have to adapt their strategies in response to the COVID-19 crisis, with a focus on resilience, agility, and innovation to ensure their survival and future growth in these challenging times. Findings follow a 10-theme style covering the research questions. The outcomes and lessons learned from this study serve as an eye-opener to Lebanese managers, leaders, researchers, and policymakers in the area of proactivity to confront future crises.